1988
DOI: 10.1126/science.2459773
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Acceptor Identity of a Transfer RNA by Altering Nucleotides in a "Variable Pocket"

Abstract: The specificity of tRNA(Arg) (arginine transfer RNA) for aminoacylation (its acceptor identity) were first identified by computer analysis and then examined with amber suppressor tRNAs in Escherichia coli. On replacing two nucleotides in tRNA(Phe) (phenylalanine transfer RNA) with the corresponding nucleotides from tRNA(Arg), the acceptor identity of the resulting tRNA was changed to that of tRNA(Arg). The nucleotides used in the identity transformation occupy a "variable pocket" structure on the surface of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 24 publications
4
121
0
Order By: Relevance
“…In addition to this, it has been demonstrated that E. coli tRNA Phe can only be alanylated by E. coli AlaRS if the acceptor stem is mutated so that it contains the G3:U70 base pair (24,29). The predicted cloverleaf structure of pneumococcal tRNA Phe indicates the presence of an unusual wobble base pair in its acceptor stem, U4:C69, which is not found in E. coli tRNA Phe (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, it has been demonstrated that E. coli tRNA Phe can only be alanylated by E. coli AlaRS if the acceptor stem is mutated so that it contains the G3:U70 base pair (24,29). The predicted cloverleaf structure of pneumococcal tRNA Phe indicates the presence of an unusual wobble base pair in its acceptor stem, U4:C69, which is not found in E. coli tRNA Phe (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of this assumption is by no means guaranteed, however. For instance, in vivo and in vitro tRNA identity conversion experiments (Giegé et al, 1998;Hou and Schimmel, 1988;McClain and Foss, 1988;McClain et al, 1991;Normanly et al, 1992) ascertained that functional equality or differences can be revealed irrespective of sequence similarities. It is known that tRNAs that have quite similar sequences may be charged by different amino acids, whereas some isoacceptor tRNAs are quite dissimilar if compared using sequential information.…”
Section: Discussionmentioning
confidence: 99%
“…The tertiary core regions of a number of class I and class II tRNAs are also implicated as specificity determinants for aminoacyl-tRNA synthetases+ Direct contact with the extra arm of tRNA Ser (Asahara et al+, 1994;Biou et al+, 1994) provides recognition in this class II tRNA+ In class I tRNAs, the variable pocket nucleotides 16,17,20,59, and 60 at the junction of the D and T-loops form a recognition site for E. coli tRNA Arg and yeast tRNA Phe (McClain & Foss, 1988a;Sampson et al+, 1989)+ Important identity elements are also known in other parts of the core region, for the class I species E. coli tRNA Phe , tRNA Glu , tRNA Ile , and tRNA Cys (McClain & Foss, 1988b;Peterson & Uhlenbeck, 1992;Hou et al+, 1993;Nureki et al+, 1994;Sekine et al+, 1996)+ One identity switch involving introduction of a long variable arm into a class I tRNA has been reported (Achsel & Gross, 1993)+ In this study, identity determinants of human tRNA Ser were inserted into human tRNA Val , and the requirements for serylation and maturation evaluated+ In addition to the large variable arm, 13 further nucleotides were necessary to confer efficient serylation capacity on the chimeric molecule+ Ten of these nucleotides, located in the D and T stems, appear important for maintaining the tertiary fold as assessed by efficiency of pre-tRNA processing in in vitro extracts+ Valylation was abolished upon introduction of the variable arm, and its possible reconstitution with further nucleotide substitutions was not studied+ Thus, this work establishes a precedent for introduction of a naturally-occurring large variable loop into a class I tRNA, but does not separate nucleotides required for stable folding from those specifying aminoacylation identity (identity elements of human tRNA Val are unknown)+ An important test of our understanding of the nucleotides specifying class I versus class II tRNA folds is the interconversion of these frameworks while retaining function+ To address this we have chosen the E. coli glutaminyl-tRNA synthetase (GlnRS)-tRNA Gln complex as a model system+ The structure of this synthetasetRNA complex is determined at a resolution of 2+5 Å (Rould et al+, 1989(Rould et al+, , 1991, with all nucleotides of the tRNA core region well resolved+ Identity determinants for tRNA Gln reside primarily in the acceptor end and anticodon loop (Jahn et al+, 1991;Hayase et al+, 1992;Ibba et al+, 1996;Sherman et al+, 1996), and interactions of GlnRS with the globular hinge occur only with the D-stem, D-stem/anticodon stem junction, and 59 D-loop nucleotides+ Integrity of the D-stem, as assessed by the introductio...…”
Section: Introductionmentioning
confidence: 99%